Cosmic-ray interactions and dating of meteorite stranding surfaces with cosmogenic nuclides - Reedy, R. C. (Los Alamos National Laboratory, 1988)
A wide variety of products from cosmic-ray interactions have been measured in terrestrial or extraterrestrial samples. These ''cosmogenic'' products include radiation damage tracks and rare nuclides that are made by nuclear reactions. They often have been used to determine the fluxes and composition of cosmic-ray particles in the past, but they are usually used to study the history of the ''target'' (such as the time period that it was exposed to cosmic-ray particles). Products made by both the high-energy galactic cosmic rays and energetic particles emitted irregularly from the Sun have been extensively studied. Some of these cosmogenic products, especially nuclides, have been or can be applied to studies of Antarctic meteorite stranding surfaces, the ice surfaces in Antarctica where meteorites have been found. Cosmogenic nuclides studied in samples from Antarctica and reported by others elsewhere in this volume include those in meteorites, especially radionuclides used to determine terrestrial ages, and those made in situ in terrestrial rocks. Cosmogenic nuclides made in the Earth's atmosphere or brought in with cosmic dust have also been studied in polar ice, and it should also be possible to measure nuclides made in situ in ice. As an introduction to cosmogenic nuclides and their applications, cosmic rays and their interactions will be presented below and production systematics of cosmogenic nuclides in these various media will be discussed later. 20 refs., 2 tabs.